Concepts of Pathology from Ancient India-A Review of Sanskrit Literature - Lahori, Mega (Annals of Pathology and Laboratory Medicine, 2022)
Contribution by ancient physicians from the Indian subcontinent towards the field of pathology has been largely unknown globally. This paper aims at providing a glimpse of the knowledge possessed by the Sanskrit scholars of ancient times (derived from Sanskrit texts written originally between 1500 B.C. and 1500 A.D) regarding the basis of disease and correlating their ideas with our present understanding of the concepts in Pathology. Ayurveda (traditional Indian medicine) was developed in India during the Vedic age (approximately 1500-500 BC). The early ayurvedic practitioners gave due importance to etiopathogenesis of diseases as a separate field called Nidana-shastra. (NidÄna means etiology or cause). Charaka emphasized that illness is caused by imbalance of the three principles (doshas) - vata, pitta and kapha, and that genetic defects are transmitted by either the sperm or the ovum. Sushruta depicted various modes of communicable disease transmission - physical contact, exhaled air, close contact, fomites etc, Madhava classified diseases based on pathogenesis (primary or secondary), etiology (endogenous or exogenous) and prognosis (curable, incurable, mild and acute). Chakrapani propounded that epidemics in a community occur due to deterioration of factors that are common to all who inhabit that community- namely air, water, soil, food, etc. Vagabhatta emphasized the importance of personal hygiene and proper nutrition for good health and elaborated the role of contaminated river water in several diseases. Agada tantra is the science of poisons and their antidotes which was founded by Kashyapa.